2008
DOI: 10.1002/jrs.2112
|View full text |Cite
|
Sign up to set email alerts
|

Molecular orientation evolution during low‐density polyethylene blown film extrusion using real‐time Raman spectroscopy

Abstract: Real-time polarized Raman spectroscopy was used in this study to measure the molecular orientation evolution during blown film extrusion of low-density polyethylene (LDPE). Spectra were obtained at different locations along the blown film line, starting from the molten state near the die and extending up to the solidified state near the nip rolls. The trans C-C symmetrical stretching vibration of polyethylene (PE) at 1132 cm −1 was analyzed for films possessing uniaxial symmetry. For the given peak, the princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
3
8
0
Order By: Relevance
“…It is also important to note that significant orientation occurs past the FLH, even after the bubble has solidified. This result is consistent with our earlier study [6] using real‐time Raman spectroscopy, which confirmed that uniaxial orientation parameters ( P 2 , P 4 ) increase along the axial distance in the film line even past the FLH. Thus, refinement of chain orientation continues even after the blown film diameter is locked into place.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…It is also important to note that significant orientation occurs past the FLH, even after the bubble has solidified. This result is consistent with our earlier study [6] using real‐time Raman spectroscopy, which confirmed that uniaxial orientation parameters ( P 2 , P 4 ) increase along the axial distance in the film line even past the FLH. Thus, refinement of chain orientation continues even after the blown film diameter is locked into place.…”
Section: Resultssupporting
confidence: 93%
“…The orientation factors corroborate the effect of stress on the orientation within the bubble for two different take‐up speeds. The orientation profiles are consistent with earlier polarized Raman spectroscopy results [6] and small‐angle light scattering [26], and confirm that orientation takes place even past the FLH during the film blowing process. These results provide a fundamental understanding of the microstructural transformation occurring during the process.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the as-spun (undrawn) state, the filaments are in a highly un-oriented condition and this expected high degree of isotropy is confirmed in Figure 6 by the fact that the : ratios are close to 1 for all vibration bands under consideration, where a value close to 1 implies that the intensities of the polarized Raman bands in the two directions are indistinguishable [44]. Further, Figure 6 shows that as the draw ratio increases, the polarization ratio for spectroscopic bands located along the polymer backbone such as for C-C stretching (ν C-C ) as well as CH 2 rocking (ρ CH2 ) and twisting (τ CH2 ) decreases for both COP and CoPA, a trend clearly observed by other authors for highly oriented fibers and films [43][44][45][46]. In contrast, Figure 6b shows how the polarization ratio obtained from the secondary amide C=O stretching vibration band located at 1638 cm -1 is directly proportional to the degree of draw ratio imparted to the CoPA fiber.…”
Section: Polarized Raman Spectroscopysupporting
confidence: 54%
“…Recently, efforts to monitor the structure evolution during film blowing in real time have been made, using techniques such as small-angle light scattering (Bullwinkel et al, 2001), Raman spectroscopy (Gururajan & Ogale, 2009) or X-ray diffraction using sealed tubes (Gururajan et al, 2008). While the advantages of using commercial X-ray sources for structural analysis are evident, they still lack the collimation which is so beneficial when using synchrotron radiation.…”
Section: Film Blowingmentioning
confidence: 99%